2014
DOI: 10.1103/physrevd.90.024008
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of a BTZ black hole solution with a Horndeski source

Abstract: In three dimensions, we consider a particular truncation of the Horndeski action that reduces to the Einstein-Hilbert Lagrangian with a cosmological constant Λ and a scalar field whose dynamics is governed by its usual kinetic term together with a nonminimal kinetic coupling. Requiring the radial component of the conserved current to vanish, the solution turns out to be the BTZ black hole geometry with a radial scalar field well defined at the horizon. This means in particular that the stress tensor associated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 21 publications
3
89
0
Order By: Relevance
“…Per se this does not guarantee the existence of a solution, but shows self-consistency of the method. Indeed, in a number of works [16][17][18], other black hole solutions with a time-dependent Galileon have been found.…”
Section: Introductionmentioning
confidence: 99%
“…Per se this does not guarantee the existence of a solution, but shows self-consistency of the method. Indeed, in a number of works [16][17][18], other black hole solutions with a time-dependent Galileon have been found.…”
Section: Introductionmentioning
confidence: 99%
“…[15] and [16] or in the case of a particular truncation of the Horndeski theory [17]. Although, Lifshitz black holes can be found analytically, and their temperature as well as their entropy can be easily computed, their thermodynamics issue remains an hard task.…”
Section: Introductionmentioning
confidence: 99%
“…A different way to bifurcate no hair theorems is to involve scalar tensor interactions involving translational invariant Galileons such as the John term of Fab 4 which reads, G µ ν ∇ µ φ∇ ν φ where G µν is the 4 dimensional Einstein tensor. There when one considers additionally a linear time dependence of the scalar field [27] (see also [28][29][30][31][32][33][34], and [35][36][37][38][39][40][41]) it was shown that the time dependence yielded analytic GR like black holes with additionally well defined scalars on the black hole horizon. For a recent review on black holes and scalar fields see [42] and [43].…”
Section: Introductionmentioning
confidence: 99%